Maʿālim wa mawāqiʿ Janūb Jazīrat Jarba - Drine, Ali (al-Jazira, 2001)
Keywords: Antiquité; Archéologie – Djerba; Monuments – Djerba

Aperçu succinct sur le fortin du site de Lalla Thala à Djerba (Tunisie) - Akkari-Weriemmi, Jenina (Africa : Revue des Études et Recherches préhistoriques, antiques, islamiques et ethnographiques, 2001)
Keywords: Antiquité; Archéologie – Djerba

Villas, wine and kilns: the landscape of Jerba in the late Hellenistic period - Fentress, Elizabeth (Journal of Roman Archaeology, 2001)
The island of Jerba emerges unobtrusively from its shallow waters. The landscape is flat, the vegetation varies from scrubland to sparse palms to large olive trees whose ample root-stocks suggest several centuries of life. The olive groves are ploughed to allow every possible drop of water to reach the roots. Dry farming of cereals is more or less pointless although, when rain is plentiful, barley will be thinly sown on land that is otherwise uncultivated. In this driest of Mediterranean zones, plentiful rain is barely more than the few showers which the 200-mm isohyet would suggest. In the interior of the island a few estates maintain irrigated cultivation, the luxuriant results of which recall Pliny's description of the oasis of Tacape; palms shelter fruit trees, which shelter pomegranates, which in turn shelter little vegetable plots. Wells provide water for these systems, the water trickling into the gardens through tiny channels (sāqiya). Today the water is pumped, but in the past each bucket had to be laboriously raised by mules or camels; their ramps form a distinctive component of the systems. High walls of mud (ṭābiya) enclose the irrigated gardens. However, in spite of the technological improvements, these gardens are less plentiful than in the past and, as the water table falls, it is more common to find an abandoned well than one in use.
Keywords: Antiquité; Archéologie – Djerba